Hastings Alumni and Fresno County Bar Association Joint Luncheon with California Supreme Court Justice Wiley Manuel - Watkins, Howard::::::::: (1979)
Post luncheon-Baxter Richardson, Howard Watkins, Justice Wiley Manuel